Dinâmica hidrossedimentológica e recomposição florística no talude da margem direita do rio São Francisco - SE - Santos, Maria Hosana dos (2016)
Change in hydrossedimentological system of the lower course of the São Francisco river, by controlling the flow, has changed the characteristics of the aquatic ecosystem as well as the suspended sediment load. The objective of this study was to evaluate the suspended sediment load in the São Francisco river Chanel, and settlement of aquatic macrophytes species in a section of the right bank under different soil bioengineering techniques. The study area comprises a margin stretch of the São Francisco River in its lower course, located in the Amparo de São Francisco Municipality, Sergipe. The botanical material collection followed conventional methods, being held from April 2014 to September 2015, in a total of four sampling time, two in the rainy season and two in the dry season. Suspended sediments load were evaluated through 03 years (2013, 2014 and 2015) in 20, 40 and 60% of the channel depth in five different transects oriented by the presence or absence of erosion control techniques, as identified: 1- Vegetated Slope; 2- Vegetated Riprap; 3- Eroded Slope; 4- Cribwall; and 5- Vetiver grass Line, considering three of them (2, 4 and 5) with soil bioengineering techniques. In the collected material 66 species was identified in 23 families, showing the its richness and diversity in a small stretch of the São Francisco River. In assessing the macrophytes population, the wet period showed greater species richness, and among soil bioengineering techniques, the Cribwall presented the highest number of individuals. The sediment load was statistically different for the three evaluated years, and the highest values were presented in 2013, when the river had the highest discharge. Among the treatments, the Eroded Slope presented at a depth of 20% the lowest contribution of suspended sediment and the Vegetated Riprap the lower sediment load rate compared to other techniques. The strong presence of aquatic macrophytes in the river contributed to the protection of the slopes toe by dissipating the energy of the ebb and flow of the waves. A progressive decrease in total sediment suspended load was found throughout evaluated period, due not only to reduced river discharge, but also the protection provided by adopted erosion control techniques.